Ta'kid Al-Madh Bima Yusybih Al-Dzamm dan Ta'kid Al-Dzamm Bima Yusybih Al-Madh: (Mempertegas Pujian dengan Nuansa Hinaan dan Mempertegas Hinaan dengan Nuansa Pujian) - Lola Irnis Lorenza; Rafly Syahputra; Harun Al-Rasyid (Jurnal Bintang Pendidikan Indonesia, 2025)
This article examines two significant linguistic phenomena in Arabic: Ta'kid Al-Madh Bima Yusybih Al-Dzamm and Ta'kid Al-Dzamm Bima Yusybih Al-Madh. Both are rhetorical techniques that enrich the meaning of praise and insult, by presenting conflicting nuances. Ta'kid Al-Madh Bima Yusybih Al-Dzamm describes the way praise is conveyed by inserting elements that contain insults, creating irony and complexity in the message. For example, expressions that appear positive can contain deep innuendo. In contrast, Ta'kid Al-Dzamm Bima Yusybih Al-Madh shows how insults can be framed with nuances of praise, turning criticism into something more subtle and open to acceptance. The research method used by researchers in this research is a qualitative research approach with a descriptive method approach. This research used data collection by searching in journals and books as well as previous research literature related to this research. Through analysis of linguistic structures and examples from literary works and everyday conversations, this article aims to explain the emotional and social impact of both techniques. With a deeper understanding of Ta'kid Al-Madh and Ta'kid Al-Dzamm, readers are expected to be able to appreciate the uniqueness and complexity of the Arabic language as well as the rhetorical implications that exist in everyday communication.